To find the table that represents \( y = f(-x) \), we need to understand what this transformation does to the graph of the function. The transformation \( f(-x) \) takes the values of the function and reflects them across the y-axis.
This means when substituting \( -x \) into the function, the output of the function will be the same as the output for \( x \) but will have the input values inverted in sign.
To analyze the options:
- For \( x = 1 \): check \( f(-1) \)
- For \( x = 2 \): check \( f(-2) \)
- For \( x = 3 \): check \( f(-3) \)
If the original function \( f(x) \) gives us values like \( f(1) \), \( f(2) \), and \( f(3) \), then \( f(-1) = f(1) \), \( f(-2) = f(2) \), and \( f(-3) = f(3) \).
If we have a function output table for \( y = f(x) \):
- \( f(1) = 2 \)
- \( f(2) = 0 \)
- \( f(3) = 2 \)
Then for \( f(-x) \):
- \( f(-1) = f(1) = 2 \)
- \( f(-2) = f(2) = 0 \)
- \( f(-3) = f(3) = 2 \)
Based on the reflection across the y-axis, we would find that \( f(-x) \) is:
- \( f(-1) = 2 \)
- \( f(-2) = 0 \)
- \( f(-3) = 2 \)
Thus, the correct table that represents \( y = f(-x) \) is:
x \( f(-x) \)
-1 2
-2 0
-3 2
Which corresponds to the third response option you listed:
- x \( f(-x) \)
-1 2
-2 0
-3 2